The Diversity of Dragonflies (Odonata) in the Joben Resort Area, East Lombok - Juni Kartini; Syachruddin Syachruddin; Mohammad Liwa Ilhamdi (Jurnal Biologi Tropis, 2022)
Dragonfly is a family of insects that are closely related to water. During their life cycle, especially when laying eggs and at the stage of dragonfly nymphs, they spend their lives in healthy water areas because dragonfly nymphs are very sensitive to polluted water quality. Therefore, dragonflies have an important role for the sustainability of the ecosystem, namely acting as predators and indicators of environmental pollution. The high diversity of dragonflies in an area indicates that the area is still not polluted because the environment supports the life of dragonflies. This study aims to determine the diversity of dragonflies (odonata) in the Joben Resort area of ​​East Lombok. This research is an exploratory descriptive study conducted from November to December 2021. Data collection was carried out 4 times and was repeated within 1 month in the morning and evening (08.00-17.00 WITA). The method used is a survey method with a sweeping net technique following a 500 m research path on 3 research paths, namely lane 1 (the river that borders Joben Ecopark), lane 2 (the path leading to the Resort Office and Joben Ecopark) and lane 3 (the river that flows through Joben Ecopark). Bordered by rice fields and Kokok Joben Brain Baths). The calculation of the diversity index of dragonflies uses the Shannon-Wienner formula (H'). The results showed that the types of dragonflies (odonata) found in the Joben Resort Area consisted of 20 species with a total number of individuals found from 3 lanes as many as 864 individuals. The diversity index of dragonflies in the Joben Resort area of ​​East Lombok is 2,309. The conclusion is that the diversity of dragonflies in the Joben Resort area of ​​East Lombok is in the medium category.